PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH, DAN BIAYA OPERASIONAL TERHADAP RETURN ON ASSET BANK UMUM SYARIAH DAN UNIT USAHA SYARIAHDI INDONESIA - Ika Meutia; Syawal Harianto; Khairil Fata (el-Amwal, 2018)
This study aims to explain the Influence of Murabahah Financing, Mudharabah, and Operational Costs on Return On Assets of Sharia Commercial Bank and Sharia Business Unit in Indonesia period 2014-2017. The sample technique used is the sample census, where the entire population is taken into a sample. The sample is 13 sharia commercial banks and 21 units of sharia business. This research data is sourced from sharia banking statistics obtained from official website of Otoritas Jasa Keuangan (OJK). Data analysis technique using multiple linear regression analysis. Where previously classic assumption test has been performed which includes normality test, multicollinearity test, and heteroscedasticity test. The result of F test shows that simultaneously Murabahah, Mudharabah, and Operational Cost variables have significant effect on return on asset. The result of t test shows that partially murabahah financing variables have positive and significant effect to return on asset, mudharabah have positive and not significant return on asset, and operational cost have negative and not significant effect to return on asset.